2013
DOI: 10.1590/s0104-11692013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Associations among occupational roles, independence, assistive technology, and purchasing power of individuals with physical disabilities

Abstract: Objective: to verify whether there are associations among occupational roles, independence to perform Activities of Daily Living, purchasing power, and assistive technology for individuals with physical disabilities. Method: 91 individuals with physical disabilities participated in the study. The instruments used were: Role Checklist, Brazilian Economic Classification Criterion, Barthel Index, and a Questionnaire to characterize the subjects. Results: an association with a greater number of roles was found amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
2
1
3
Order By: Relevance
“…We examined whether the use of AT could improve participation in social activities, but our results indicate no statistically significant differences between users and non-users. This contrasts with studies that have found that AT use improves social engagement 1,5 , but it is similar to another study that found that assistive devices in Brazil did not improve independence 21 . As highlighted in a systematic review of studies addressing the use of walking devices and social participation, AT use only seems to facilitate social participation and engagement when users integrate them into their everyday lives 1 .…”
Section: Discussioncontrasting
confidence: 60%
“…We examined whether the use of AT could improve participation in social activities, but our results indicate no statistically significant differences between users and non-users. This contrasts with studies that have found that AT use improves social engagement 1,5 , but it is similar to another study that found that assistive devices in Brazil did not improve independence 21 . As highlighted in a systematic review of studies addressing the use of walking devices and social participation, AT use only seems to facilitate social participation and engagement when users integrate them into their everyday lives 1 .…”
Section: Discussioncontrasting
confidence: 60%
“…Functional capacity is extremely important for the realization of various roles in society and for the improvement of quality of life (20)(21) . A research conducted with patients after the first CVA emphasizes the importance and proposes a model of care to the patient that goes from hospitalization to a plan of discharge; home care, referring to the assistance by the Family Health Strategy (FHS); informal care, involving the action of the family and other who take care of the patient; and self-care, which includes educational strategies so that dependence is minimized until independence is achieved (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The scale ranges from zero (0) to 100, whereby 0 means total dependence and 100 complete independence in the assessed dimensions. In the literature, different cut-off scores have been defined as indicators for interventions or for the identification of a risk [19,20]. The subject of this study was the BI according to the Hamburg Classification Manual.…”
Section: Introductionmentioning
confidence: 99%